Electron flow from PSII to PSI under high light is controlled by PGR5 but not by PSBS - Tikkanen, Mikko; Rantala, Sanna; Aro, Eva-Mari (Frontiers in Plant Science, 2015)
Absence of the PROTON GRADIENT REGULATION 5 (PGR5) protein from plant chloroplasts prevents the induction of strong trans-thylakoid proton gradient (ΔpH) and consequently also the thermal dissipation of excess energy (NPQ). The absence of the PSBS protein likewise prevents the formation of ΔpH-dependent NPQ. This component of NPQ is called qE, which is nearly exclusively responsible for induction of NPQ upon increase in light intensity. On the other hand, the pgr5 mutant is not only deficient in induction of strong NPQ but it also lacks the capability to oxidize P700 upon increase in light intensity. This, in turn, results from uncontrolled electron flow towards PSI, which has been proposed to be caused by the lack of PSII down-regulation by NPQ and by a poor control of electron flow via the Cytochrome b6f (Cyt b6f) complex. Here we asked whether NPQ really is a component of such regulation of electron flow from PSII to PSI at high light. To this end, the two NPQ mutants pgr5 and npq4, the latter lacking the PSBS protein, were characterized. It is shown that the npq4 mutant, despite highly reduced PQ pool, does not inhibit but rather enhances the oxidation of P700 in high light as compared to wild type. This clearly demonstrates that the control of electron flow from PSII to PSI cannot be assigned, even partially, to the down-regulation of PSII by NPQ but apparently takes place solely in Cyt b6f. Moreover, it is shown that the pgr5 mutant can induce NPQ in very high light, but still remains deficient in P700 oxidation. These results challenge the suggestion that NPQ, induced by PGR5-dependent cyclic electron transfer, would have a key role in regulation of electron transfer from PSII to PSI. Instead, the results presented here are in line with our recent suggestion that both PSII and PSI function under the same light harvesting machinery regulated by ΔpH and the PSBS protein (Tikkanen and Aro 2014; Grieco, et al., 2015).